Eritrea 2003 Article IV Consultation Staff Report : 2003 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Eritrea. (IMF Staff Country Reports; Country Report, 2003)
The Eritrean economy continues to be adversely affected by the effects of the border conflict with Ethiopia. In other structural reform areas, the government seems to have further increased state control over the economy. The authorities confirmed their commitment to strengthen the role of the private sector, but they believed that the sector was not yet ready to take the lead in a number of critical areas. The preparation of a medium-term macroeconomic outlook was beset by a number of difficulties, including, in particular, the lack of timely and reliable data.